Adeno-associated virus-mediated cancer gene therapy: Current status. Issue 2 (28th January 2015) - Luo, Jingfeng; Luo, Yuxuan; Sun, Jihong; Zhou, Yurong; Zhang, Yajing; Yang, Xiaoming
Highlights: The latest developments of AAV vectors were presented. Latest issues of AAV-mediated gene therapy for cancers were summarized. Up to date knowledge on the clinical trials of AAV-mediated gene therapy were reviewed. Abstract: Gene therapy is one of the frontiers of modern medicine. Adeno-associated virus (AAV)-mediated gene therapy is becoming a promising approach to treat a variety of diseases and cancers. AAV-mediated cancer gene therapies have rapidly advanced due to their superiority to other gene-carrying vectors, such as the lack of pathogenicity, the ability to transfect both dividing and non-dividing cells, low host immune response, and long-term expression. This article reviews and provides up to date knowledge on AAV-mediated cancer gene therapy.